Pola Menstruasi Dengan Kejadian Akne Vulgaris Pada Siswi SMKN Tanjungsari Lampung Selatan Tahun 2020 - Ridho Pangestu; Nopi Sani; Arti Febriyani; Resati Nando Panonsih (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Acne vulgaris (AV) is a disease that can grow alone in the form of chronic inflammation of polysebaceous follicles with multifactorial causes and clinical manifestations in the form of comedones, papules, pustules, nodules, and cysts. In adolescence, AV is usually caused by an increase in sex hormones, especially androgens, which increase during puberty. Aim; This study aims to determine the relationship between menstrual patterns and the incidence of acne vulgaris in State Vocational High School students. Method; using an observational research design using a cross-sectional approach. The number of samples in this study was 80 samples. The sampling technique in this study used simple random sampling. The instrument used is a questionnaire sheet. Analysis of the data used is the chi-square test. Results: menstrual pattern on the incidence of acne vulgaris was 0.091 (p>0.05). Conclusion: That there is no significant relationship between menstrual patterns and the incidence of acne vulgaris in students of SMKN